MODEL PERLINDUNGAN HUKUM BAGI KREDITUR LAYANAN PINJAM MEMINJAM UANG BERBASIS TEKNOLOGI INFORMASI DI MASA PANDEMI COVID-19 - Debbi Puspito; Martin Roestamy; Edy Santoso (Magister Hukum Sekolah Pascasarjana Unida, 2022)
The purposes of this study are 1) to find out and analyze the forms of violations committed by fintech lending debtors online during the Covid-19 pandemic; 2) to find out and analyze the legal protection model for creditors in these services during the Covid-19 pandemic. The research method used is normative juridical analysis with a descriptive analysis approach. The results of this study are: 1). There are 3 types of violations encountered during the loan service research, namely default in the form of default by the debtor at the time of repaying the loan for several reasons, including not having a fixed income while the debtor needs funds for his daily needs. Another problem is the existence of bad faith from third parties (sales), committing fraud violations with fictitious debtor data and deliberately failing to pay 2). Legal protection models that can be applied include: Financial protection in the form of insurance for creditors; Guarantee Protection in the form of intangible assets in the form of a National Identity Number; Agreement protection, namely strengthening the position of creditors in the contents of the agreement: and protection of strict sanctions contained in the legislation.